NILAI PESSE: SEBUAH MODEL UNTUK MEMBANGUN KARAKTER ANAK DI SEKOLAH - Lebba Lebba (JURNAL ILMU BUDAYA, 2022)
This study aims to explain the inheritance of pesse' value ​​as a model of empathy in building the character of students at schools. After the revitalization of local wisdom has been carried out, it will then reduce the cultural characteristics between generations. In the inheritance of "pesse" value, the model that can be used is the Cavalli-Sforza and Feldman (1981) inheritance model which includes three processes. The stage of inheritance of pesse' value ​​at a macro level must continue to reproduce to form and to perpetuate an anti-violence habitus. Thus, the inculcation of pesse' value ​​in schools must become a common framework of all stakeholders, parents, schools, government, and other stakeholders, to synergize in developing the values ​​of “pesse” in generations as an effort to cut the reproduction of violent habitus, especially among students in Makassar, South Sulawesi.